2002
DOI: 10.1128/jcm.40.10.3694-3702.2002
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rapid Immunodiagnostic Test for Haemophilus ducreyi

Abstract: Haemophilus ducreyi is the etiologic agent of chancroid, a sexually transmitted disease that increases the rate of transmission of human immunodeficiency virus. Chancroid ulcerations are difficult to distinguish from those produced by syphilis and herpes. Diagnosis based solely on clinical grounds is inaccurate, and culture is insensitive. Highly sensitive PCR has largely superseded culture as the preferred method of laboratory diagnosis; however, neither culture nor PCR is feasible where chancroid is endemic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
0
20
0
1
Order By: Relevance
“…Plasmids expressing hgbA with a leader sequence are unstable in E. coli (data not shown). Moreover, these inclusion body-derived (IBD) rHgbA proteins are not recognized by conformation-dependent antinHgbA monoclonal antibodies (20), IBD rHgbA does not bind Hb, and antibodies elicited to IBD rHgbA do not recognize whole cells of H. ducreyi (data not shown). To avoid these issues, we decided to express hgbA from plasmids in H. ducreyi.…”
Section: Resultsmentioning
confidence: 99%
“…Plasmids expressing hgbA with a leader sequence are unstable in E. coli (data not shown). Moreover, these inclusion body-derived (IBD) rHgbA proteins are not recognized by conformation-dependent antinHgbA monoclonal antibodies (20), IBD rHgbA does not bind Hb, and antibodies elicited to IBD rHgbA do not recognize whole cells of H. ducreyi (data not shown). To avoid these issues, we decided to express hgbA from plasmids in H. ducreyi.…”
Section: Resultsmentioning
confidence: 99%
“…HgbA is also required for expression of full virulence in the temperature-dependent rabbit model (59) and the human model of chancroid (5). Patterson et al (44) reported that HgbA was highly conserved, since three antiHgbA Mabs bound to all 26 strains tested. The sole exception was MAb 4.23, which bound all strains except HMC112, identified as a class II strain in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…One-liter cultures of pUNCH 1293 (dsrA I ), pUNCH 1294 (dsrA II ), and pUNCH 1295 (ncaA I ) in BL21(DE3)pLysS were grown in liquid broth with appropriate antibiotics ( Table 1). As previously described (14,44), protein expression was induced from these plasmids with IPTG. The cultures were subsequently treated with rifampin to inhibit bacterial RNA polymerase.…”
Section: Analysis Of Losmentioning
confidence: 99%
“…In Western blots, HgbA was weakly recognized with HgbA-immunized pig sera, probably due to its change in conformation after denaturation or poor transfer from the gel to nitrocellulose. Previously, we found that mouse monoclonal antibodies (44) and rabbit antisera (36) elicited to native HgbA also failed to bind in Western blots, suggesting that the conformation of HgbA is complex and critical to antibody binding. In Western blots, we also found that anti-HgbA sera recognized an unknown component of approximately 20 kDa.…”
Section: Discussionmentioning
confidence: 99%
“…Except for FX504, all strains were grown under heme-limiting conditions (GCB with 1% IsoVitaleX and 5% FBS) as described previously (19). Since the FX504 mutant does not grow under the described heme-limiting conditions, 5 g of hemin per ml was added to the above-described broth medium (44).…”
Section: Methodsmentioning
confidence: 99%